C85 IMPACT OF QUARANTINE ON CARDIOVASCULAR RISK FACTORS. (18th May 2022) - Castello, L; Di Fusco, S; Leggio, M; Alonzo, A; Aiello, A; Imperoli, G; Colivicchi, F
Abstract: Background: Pandemic–related quarantine has led to critical lifestyle changes with possible detrimental consequences on health. The effects of lockdown on cardiovascular (CV) risk factors have been investigated to define patient–tailored strategies aimed at reducing the negative impact on CV health. Methods: We administered a closed response survey to consecutive patients coming to our cardiac outpatient centre over a period of 10 days. Questions focused on quarantine–related lifestyle changes during March and April 2020. Results: We enrolled 150 patients (62% male, mean age 65 years). The vast majority of subjects (73%) did not work due to retirement/unemployment, 14% worked in office and 13% worked from home. 50% had hypertension and/or diabetes and/or dyslipidemia, 33% had atrial fibrillation, 17% coronary artery disease, 6% had heart failure and 4% had a pacemaker/ICD implanted. Physical activity did not change for 44%, increased in 2%, decreased in 33% and was stopped in 21%. Dietary pattern remained the same in 73% while 22% consumed more junk food and 5% more healthy food. Body weight was not monitored in 35%, remained unchanged in 32%, increased in 28% and decreased in 5%. Among active smokers (22%), 86% reported higher cigarette consumption while 14% reduced/unchanged number of cigarettes per day. Sleep disorders were present in 73%. Regarding health needs, 16% had to reschedule medical check–ups due to personal choice or hospital unavailability. Conclusions: Quarantine appeared to have different effects on CV risk factors. During lockdown, on–site work was limited, which may partially account for the observed lifestyle changes. Physical activity was reduced/interrupted in more than half of the population, whereas dietary pattern did not change in the vast majority of subjects, with only a small proportion reporting worse dietary habits. Body weight increased in only a minority of subjects, though this may be underestimated because most participants did not monitor their weight. Cigarette consumption was higher for the majority of active smokers. Similarly, sleep disorders were present in the vast majority of subjects. To conclude, consistent with current literature, our real–world data confirm that quarantine seems to have affected lifestyle habits defining CV risk profile differently. A patient–tailored approach should be implemented to minimise possible detrimental effects of quarantine on CV health.